Public Firms as Regulatory and Auditing Instruments - Devon Garvie; Roger Ware (Queen's University, Department of Economics, 1991)
We re-examine the regulatory role of a public firm in an environment of private but correlated information about industry costs. We study three regimes of mixed market interaction involving both public and private firms: a symmetric Bayesian-Nash equilibrium, an asymmetric Bayesian equilibrium in which the public firm is able to commit to production before the private firms and a mechanism in which the regulator designs an incentive compatible schedule for the industry. We find that a public firms plays an important strategic informational role which strengthens its role as a disciplinary regulatory instrument. Further, we find that this strategic informational role is considerably enchanced as we move from indirect regulatory schemes to direct regulation.
Keywords: 330